SAFETY OF INACTIVATED POLYMER-SUBUNIT THREE VALENCE INFLUENZA VACCINE. POSTREGISTRATIONAL OBSERVATION - S.M. Kharit; E.P. Nacharova; T.V. Chernyaeva ("Paediatrician" Publishers LLC, 2009)
Clinical trial for polymer-subunit trivalent influenza vaccine Grippol plus reactogenicity assessment in 153 children aged 3-17 years old was conducted in the frames of post-registration studies. Prior to the vaccination the written informed agreement was signed by every participant' parent. In post-vaccination period physical examination and thermometry was performed daily in post-immunization days 1-5, on days 21-28 and then on a monthly basis for 4 months. Study results demonstrated that Grippol plus possesses low reactogenicity and can be applied in pediatrics for immunization in accordance with National Immunization schedule. Key words: children, influenza, vaccination. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):37-41)